How Local Governments Link Green Economy and Eco-Edu Tourism? - Joli Apriansyah; Evi Satispi; Mawar Mawar; Kurniasih Mufidayati; Lusi Andriyani (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study investigates how the green economy agenda is operationalised through eco-edu tourism along the Ciliwung River in Kelurahan Cikoko, South Jakarta. Drawing on qualitative case-study evidence, the research documents how the kelurahan initiated riverbank revitalisation by convening multi-actor collaboration involving residents and neighbourhood organisations, community groups, relevant government units, and private-sector support. Data were collected through in-depth interviews, field observations, and document review, and analysed through iterative coding (open–axial–selective) to trace how governance arrangements translated sustainability aims into practice. Empirically, the initiative transformed previously neglected riverbank segments into public eco-edu spaces featuring urban farming plots, community learning areas, and hands-on environmental programmes. Interview accounts highlight practical learning activities such as urban farming, waste management, rainwater processing, plant nurseries, and small-scale aquaculture, complemented by river-based experiential activities (e.g., river exploration/education programmes). These practices strengthened community participation and environmental literacy, while also generating micro-level economic benefits through cultivation outputs and visitor-linked activities. Persistent constraints were also identified, notably coordination burdens across institutions, limited and fragmented financing for routine maintenance, and the vulnerability of programme continuity to shifting political priorities. The study concludes that urban eco-edu tourism can function as a workable green economy instrument when cross-sector coordination is institutionalised, community co-management is supported, and resource-circular practices are embedded as visible learning infrastructure. The findings offer actionable implications for metropolitan governments seeking to implement green economy initiatives through community-based, education-oriented urban tourism.